The Implicature of Indonesian Financial Transaction Reports and Analysis Center Authority to Freeze Bank Accounts on Citizens’ Constitutional Rights: A Democratic Rule of Law Perspective - Rifa’i, Ahmad; Arzaqi, Nila (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This article examines the authority of Indonesia’s Financial Transaction Reports and Analysis Center (INTRAC) to freeze bank accounts as a preventive measure against money laundering and related crimes. While effective in securing illicit assets, this authority raises concerns regarding proportionality, constitutional rights, and democratic accountability, highlighting the need for balanced safeguards within Indonesia’s legal system.Purposes of the Research: The purpose of this research is to analyze the constitutional implications of INTRAC authority to freeze bank accounts, evaluate its conformity with the principles of a democratic rule of law, and propose recommendations for ensuring a balanced approach between effective financial crime prevention and the protection of citizens’ constitutional rights.Methods of the Research: This study uses a normative juridical approach supported by limited empirical insights.Findings of the Research: The findings of this study show that while INTRAC account-freezing authority is an effective preventive tool against financial crime, its lack of judicial oversight creates risks of disproportionate rights restrictions. Using implicature analysis, this research uncovers hidden consequences such as reputational harm and financial paralysis, offering an original perspective that bridges normative law with socio-political impacts in a democratic rule of law.